Temporal trends in incidence of pediatric type 1 diabetes in Alabama: 2000‐2017. Issue 1 (16th October 2019) - Correya, Tanya A.; Ashraf, Ambika P.; Griffin, Russell; Aslibekyan, Stella; Kim, Hae dong; Middleton, Sydney; McCormick, Kenneth
Abstract: Objective: The incidence of type 1 diabetes has increased in the United States and worldwide. We hypothesized that trends in the annual incidence rates of childhood‐onset type 1 diabetes in the state of Alabama would be different by race and sex. Methods: We performed a retrospective observational cohort study, analyzing children with type 1 diabetes (n = 3770) managed at the Children's Hospital of Alabama between 2000 and 2017. We compared crude incidence rates using negative binomial regression models and analyzed differences in annual trends of age‐adjusted incidence by race and sex using joinpoint regression. Results: The crude type 1 diabetes incidence rate was estimated at 16.7 per 100 000 children <19 years of age in Alabama. Between 2000 and 2007, there was an increase in age‐adjusted incidence of type 1 diabetes with an annual percent change (APC) of 10% from 2000 to 2007 and a 1.7% APC decrease from 2007 to 2017. The age‐adjusted incidence for Whites and Blacks increased with an average annual percentage change (AAPC) of 4.4% and 2.8%, respectively. A nearly 11% increasing trend in age‐adjusted incidence was observed for both races, though the increase plateaued in 2006 for Whites and 2010 for Blacks. Conclusions: Following significantly increasing annual trends for both races, the age‐adjusted rate remained statistically stable for Whites and decreased significantly for Blacks. Longer‐sustained trend increases for Blacks resulted in type 1 diabetes incidence tripling compared to the doubling of the rate for Whites.